The fund established to respond to loss and damage from climate change: Ethiopia’s preparedness in data management and robust scientific information production - Engdaw, Mastawesha Misganaw (2025)
This Feature highlights the disproportionate burden of climate change-induced loss and damage on low-income and developing countries, particularly Ethiopia. While industrialized nations are the primary contributors to greenhouse gas emissions, it is the least emitting countries that suffer the most from extreme events such as heatwaves, droughts, floods, and wildfires. These climate-induced shocks exacerbate vulnerabilities, threaten ecosystems, and disrupt livelihoods and economies. Although existing global finance mechanisms like the Adaptation Fund and Green Climate Fund offer some support, they fall short in addressing the full scale of losses and damages experienced by vulnerable nations. The establishment of the Fund for Responding to Loss and Damage (FRLD) under the World Bank offers a new opportunity for developing countries to receive financial support. However, eligibility for accessing these funds is contingent on robust, timely, and scientifically credible evidence that links climate hazards to observed losses and damages. Ethiopia, like many developing nations, faces challenges in generating and managing such data due to limited technical, financial, and institutional capacity. This Feature highlights the critical need to strengthen national data systems, build climate information management capacity, and improve the credibility of evidence as a pathway to access loss and damage financing and effectively respond to losses and damages.